Application of Optimal Preventive Replacement Age Model to Determine Replacement Schedule For Dumping Grate Component on Boiler Machine (Case Study at Rejo Agung Baru Sugar Factory Madiun) - Dania, Wike Agustin Prima; Purwaningsih, Isti; Purwaningsih, Isti; Purwaningsih, Isti; Aristiono, Fajar Andy; Aristiono, Fajar Andy; Aristiono, Fajar Andy (Jurnal Teknologi Pertanian, 2011)
Rejo Agung Baru Madiun is one of big sugar companies in East Java. One of the problems in this factory is delayed of production process caused by machine damaged. Based on preliminary survey, it showed that boiler machine is regularly damage and has the highest downtime. Moreover, component that influences the damage of boiler machine is dumping grate component. The main purpose of this research is to determine optimal replacement schedule that has minimum downtime and maximum availability of dumping grate component. Method that is used to solve the problem is optimal preventive replacement age model. Furthermore, it also determines and compares replacement cost before and after scheduling. From the result, it shows that the replacement interval for dumping grate is 555 hours or 23.125 days with the minimum downtime value is 0.010018182 and the availability value is 0.989981818. Total cost of optimal replacement scheduling is Rp 3,341,078,529.00. The cost comparison before replacement scheduling and after replacement scheduling is Rp 3,517,399,429.00 and Rp 3,341,078,529.00 respectively or saving about 5.013%. Keywords: dumping grate, minimum downtime, maximum availability, optimal preventive replacement age model